EFFECT OF SILICON RUBBER (SIR) IN FABRICATION OF NdFeB/BaFe12O19-BASED HYBRID MAGNET - Ramlan, Ramlan; Soerya, Balada; Fachredzy, Amdy; Naibaho, Marzuki; Ginting, Masno (Universitas Mataram, 2024)
The purpose of this study was to determine the effect of physical properties (density), magnetic properties (magnetic flux), and mechanical properties (tensile strength) of NdFeB- BaFe12O19 hybrid magnets with silicon rubber adhesive. NdFeB - BaFe12O19 permanent magnet has been made with a silicon rubber (SIR) adhesive mixture. The percentage variations of magnetic powder materials used are NdFeB: BaFe12O19 (95%: 5%) and NdFeB: BaFe12O19 (90%: 10%) mixed with a weight percentage of silicone rubber with variations of 20%, 40%, 60% and 80%. Characterization includes physical properties in the form of density where the sample with 20% SIR variation has the largest bulk density value of 3.28 g/cm3 for NdFeB: BaFe12O19 (95%: 5%) and 3.24 g/cm3 for NdFeB: BaFe12O19 (90%: 10%), and mechanical properties in the form of tensile strength where the most optimum elasticity value is at 80% silicone rubber. Meanwhile, the most optimum magnetic properties of materials are owned by material samples with variations of SIR at a concentration of 20% for sample variations of 95% NdFeB and 5% BaFe12O19, which is 602.8 Gauss.